The New Zealand gravimetric quasigeoid model 2017 that incorporates nationwide airborne gravimetry - McCubbine, J.; Amos, M.; Tontini, F.; Smith, E.; Winefied, R.; Stagpoole, V.; Featherstone, Will (Springer - Verlag, 2017)
A one arc-minute resolution gravimetric quasigeoid model has been computed for New Zealand, covering the region (Formula presented.)–(Formula presented.) and (Formula presented.)–(Formula presented.). It was calculated by Wong and Gore modified Stokes integration using the remove–compute–restore technique with the EIGEN-6C4 global gravity model as the reference field. The gridded gravity data used for the computation consisted of 40,677 land gravity observations, satellite altimetry-derived marine gravity anomalies, historical shipborne marine gravity observations and, importantly, approximately one million new airborne gravity observations. The airborne data were collected with the specific intention of reinforcing the shortcomings of the existing data in areas of rough topography inaccessible to land gravimetry and in coastal areas where shipborne gravimetry cannot be collected and altimeter-derived gravity anomalies are generally poor. The new quasigeoid has a nominal precision of (Formula presented.) on comparison with GPS-levelling data, which is approximately (Formula presented.) less than its predecessor NZGeoid09.